The Perception of Respondents of Intelligent Packaging in Slovakia as Ecological Innovations - Loučanová, Erika; Parobek, Ján; NosáÄ¾ováMartina; Dopico, Ana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
The research of new active and intelligent features has shown huge potential to optimise the supply chain and enhance consumer consciousness of food utilisation. The paper deals with the evaluation of the perception of intelligent packaging in Slovakia as ecological innovations through the Kano model. It focuses on to analysis the perception of different intelligent packaging features. The results indicate that customers‟ awareness of intelligent packaging is still at a very low level in Slovakia.